A State Space and Density Estimation Framework for Sleep Staging in Obstructive Sleep Apnea - Kang, Dae Y. (IEEE Trans Biomed Eng, 2017)
OBJECTIVE: Although the importance of sleep is increasingly recognized, the lack of robust and efficient algorithms hinders scalable sleep assessment in healthy persons and those with sleep disorders. Polysomnography (PSG) and visual/manual scoring remain the gold standard in sleep evaluation, but more efficient/automated systems are needed. Most previous works have demonstrated algorithms in high agreement with the gold standard in healthy/normal (HN) individuals – not those with sleep disorders. METHODS: This paper presents a statistical framework that automatically estimates whole-night sleep architecture in patients with obstructive sleep apnea (OSA) – the most common sleep disorder. Single-channel frontal electroencephalography was extracted from 65 HN/OSA sleep studies, and decomposed into 11 spectral features in 60,903 30s sleep epochs. The algorithm leveraged kernel density estimation to generate stage-specific likelihoods, and a 5-state hidden Markov model to estimate per-night sleep architecture. RESULTS: Comparisons to full PSG expert scoring revealed the algorithm was in fair agreement with the gold standard (median Cohen’s kappa = 0.53). Further analysis revealed modest decreases in median scoring agreement as OSA severity increased from HN (kappa = 0.63) to severe (kappa = 0.47). A separate implementation on HN data from the Physionet Sleep-EDF Database resulted in a median kappa = 0.65, further indicating the algorithm’s broad applicability. CONCLUSION: Results of this work indicate the proposed single-channel framework can emulate expert-level scoring of sleep architecture in OSA. SIGNIFICANCE: Algorithms constructed to more accurately model physiological variability during sleep may help advance automated sleep assessment, for practical and general use in sleep medicine.